1978
DOI: 10.1246/bcsj.51.2398
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Neobavaisoflavone and Related Compounds

Abstract: The condensation of 7-benzoyloxy-4′-hydroxyisoflavone with 2-methyl-3-buten-2-ol gave 7-benzoyloxy-4′-hydroxy-3′-(3-methyl-2-butenyl)isoflavone. The hydrolysis of the alkylated isoflavone with dilute alkali afforded neobavaisoflavone [7,4′-dihydroxy-3′-(3-methyl-2-butenyl)isoflavone], which was then converted into isoneobavaisoflavone on heating with formic acid. 7-Benzyloxy-4′-hydroxyisoflavone was condensed with 2-methyl-3-buten-2-ol to give a chroman derivative, which was then converted into isoneobavaisofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…[M]+ to be 322.1200 (caled for C20H18O4, 322.1205). A literature search showed that several prenylated flavones or isoflavones had the above formula: e.g., licoflavone A (6-C-prenyl-7,4'-dihydroxyflavone) (11), 6-C-prenylchrysin (12), and neobavaisoflavone [5] (13). That the isolated compound was indeed 5 was evident from the mp 187-191°and the ir, uv, and 'H-nmr spectra which were in accord with the literature dNitrofluorene.…”
Section: General Isolation and Characterizationsupporting
confidence: 71%
See 1 more Smart Citation
“…[M]+ to be 322.1200 (caled for C20H18O4, 322.1205). A literature search showed that several prenylated flavones or isoflavones had the above formula: e.g., licoflavone A (6-C-prenyl-7,4'-dihydroxyflavone) (11), 6-C-prenylchrysin (12), and neobavaisoflavone [5] (13). That the isolated compound was indeed 5 was evident from the mp 187-191°and the ir, uv, and 'H-nmr spectra which were in accord with the literature dNitrofluorene.…”
Section: General Isolation and Characterizationsupporting
confidence: 71%
“…'isolated at Research Triangle Institute. (13). The isoflavone nature of 5 was readily apparent from the 'H-nmr spectra, particularly the C-2 proton which appeared as a singlet at 8.26.…”
Section: General Isolation and Characterizationmentioning
confidence: 96%
“…A conventional battery of NMR experiments, including COSY, HMQC, and HMBC, was performed to confirm the gross structure of compound 18 as shown. Compound 18 differs from the known compound neobavaisoflavone (19) 30 by the presence of an additional hydroxyl group at position C-2′ and reduction of the ∆ 2 olefin; thus, we have named the new compound 2,3-dihydro-2′-hydroxyneobavaisoflavanone (18).…”
Section: A Isomalabaricane Triterpenes From a Stellettamentioning
confidence: 99%
“…All the isolates 1-20 were identified as isopsoralen (1) (Kim et al 2009), psoralen (2) (Kim, Lee, Park and Shim 2009), psoralidin (3) (Oh et al 2010), coumestrol (4) (Al-Maharik and Botting 2004), 3'-methoxycoumestrol (5) (Gong et al2010), isobavachalcone; corylifolinin (6) (Oh et al 2010;Pistelli et al 1996), 4′-O-methylbavachalcone (7) (Oh et al 2010), isobavachromene (8) (Xue-Hui et al 2012), bavachromene ( 9) (Bajwa et al 1972), bavachinin (10) (Oh et al 2010), bavachin (11) (Xu et al 2018), paratocarpin K ( 12) (Hano et al 1995), neobavaisoflavone (13) (Nakayama et al 1978;Xiao et al 2010), corylifol A ( 14) (Yin et al 2004), 8-geranyl daidzein (15) (Kumano et al 2008), 8-prenyldaidzein (16) (IINUMA et al 1992, corylifol C (17) (Yin et al 2004), bakuchiol (18) (Kim et al 2009), 3-hydroxybakuchiol (19) (Labbé et al 1996) and 12-hydroxyisobakuchiol (20) (Labbé et al 1996).…”
Section: Structure Elucidationof Isolated Phytochemical Compounds Fro...mentioning
confidence: 99%